Describing youth participatory evaluation of educational interventions as a key domain of the social determinants of health: protocol for a scoping review - Bianca Montrosse-Moorhead; Amanda Sutter; Chisomo Phiri; Luna De La Cruz Perdomo (BMJ Open)
Introduction Youth participatory evaluation is one model for monitoring global outcomes and assessing interventions to improve young people’s health equity and well-being while embracing principles of participation and empowerment. Little is known about the use of this approach in practise. This scoping review will identify and synthesise descriptions of how youth participatory evaluation is enacted, to what extent it occurs, and describe the relationship between context and inclusion.Methods and analysis Scoping review methods will adhere to those outlined by Arksey and O’Malley. The study will also follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. The review will use publicly available evaluation reports (grey literature) for programmes funded by the US National Science Foundation through the Advancing Informal science, technology, engineering and mathematics (STEM) Learning programme and whose reports are archived in the repository hosted by the Reimagining Equity and Values in Informal STEM education (REVISE) Center. This scoping review is limited to education, one of the domains of the social determinants of health, more precisely STEM education, due to the report publication parameters set by the REVISE Center repository. A research team member will download citations for and PDFs of reports. These citations and reports will be managed using Zotero and exported to Covidence, a web-based program designed to manage systematic and scoping reviews. Evaluation report selection will occur in a two-step process by trained coders with clear criteria. Inclusion criteria will include: (1) report is for an evaluation study; (2) evaluation has a focus on young people, aged 10–24; (3) evaluation is for a programme serving young people, aged 10–24; and (4) report written and uploaded to the REVISE Center repository between 2017 and 2022. All reports hosted on the REVISE Center repository are based in the USA and written in English. Data charting will also be done by trained coders and facilitated by Covidence and a codebook. Several procedures will be used to uphold rigour and consistency during this process. Data analysis will be done with Dedoose.Ethics and dissemination Human subjects research approval will not be required. This scoping review will rely on publicly available evaluation reports. No human research participants will be involved in this review. Findings will be shared through dissemination strategies, such as peer-reviewed journals, international and national conferences, and social media affiliated with academic institutions and professional associations.Study registration This study is preregistered on Open Science Framework (https://osf.io/23jdx/). Registration DOI: https://doi.org/10.17605/OSF.IO/K6J98.